2012
DOI: 10.1029/2011gl050420
|View full text |Cite
|
Sign up to set email alerts
|

Response of the polar magnetic field intensity to the exceptionally high solar wind streams in 2003

Abstract: The exceptionally high solar wind stream activity in 2003 caused a record intensity in the auroral electrojet currents, leading to a major reduction of the horizontal field at auroral latitudes and to a notable strengthening of the vertical geomagnetic field in the polar cap. This strengthening is clearly visible in the observatory annual values as a significant deflection in the corresponding secular variation. A similar but weaker deflection also occurs during the strongest high speed stream years of the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Even at monthly time scale we find high correlations between the two parameters for all months, giving evidence that other factors in solar wind, especially the intensity of the interplanetary magnetic fields which is enhanced during CMEs [Richardson and Cane, 2012], have a significantly smaller effect for the monthly averages of ΔH at Sodankylä. This supports the earlier studies which have shown the importance of the SW speed for substorm occurrence [Tanskanen et al, 2005] and high-latitude geomagnetic activity [Finch et al, 2008;Lukianova et al, 2012;Holappa et al, 2014].…”
Section: Discussionsupporting
confidence: 92%
“…Even at monthly time scale we find high correlations between the two parameters for all months, giving evidence that other factors in solar wind, especially the intensity of the interplanetary magnetic fields which is enhanced during CMEs [Richardson and Cane, 2012], have a significantly smaller effect for the monthly averages of ΔH at Sodankylä. This supports the earlier studies which have shown the importance of the SW speed for substorm occurrence [Tanskanen et al, 2005] and high-latitude geomagnetic activity [Finch et al, 2008;Lukianova et al, 2012;Holappa et al, 2014].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that solar wind speed is an important driver of long‐term (e.g., monthly and yearly) geomagnetic activity at low latitudes and midlatitude (Akasofu, ; Crooker, Feynman, & Gosling, ; Richardson, Cane, & Cliver, ; Richardson, Cliver, & Cane, ) and, especially, at high latitudes (Finch et al, ; Holappa, Mursula, & Asikainen, ; Holappa, Mursula, Asikainen, & Richardson, ; Lukianova, Mursula, & Kozlovsky, ; Mursula, Holappa, & Lukianova, ; Mursula, Lukianova, & Holappa, ) and of substorm activity (Tanskanen et al, ). Here we study to what extent the solar wind speed controls the seasonal variation of high‐latitude geomagnetic activity.…”
Section: Seasonal Variation Of Solar Wind Speed In 1995–2014mentioning
confidence: 99%
“…So far, the temporal resolution of 1 min, or at most 10 s, has been the international standard for decades (e.g., in International Real‐time Magnetic Observatory Network). The instrumentation in Greenland has recently been upgraded, and the 1‐s resolution measurements are available from a few stations since 2010 and from several stations since 2011, while the earlier, lower frequency measurements and the geomagnetic activity indices derived from them have been widely utilized (Lukianova et al, ; Mursula et al, ; Tavares et al, ). This high‐frequency data (1‐s) have been so far left unanalyzed to full detail.…”
Section: Introductionmentioning
confidence: 99%